Transitions in innovation frameworks - Mendonça, S. (Proceedings of the 2013 International Conference on Information Systems and Design of Communication, 2013)
This paper provides a partial review of the understanding of innovation in academia and policy circles. Science and technology can be said to have surfaced around the 1950s as an industrial policy tool. Dominant views on innovation began along the lines of the "Linear model", a perspective that has stayed influential. In the 1980s a major re-conceptualisation of the innovation process matured, this came with the introduction of the "chain-linked model". By the 2000s new research on innovation suggested a substantial update and revision of the concept of innovation, encapsulated by the "multi-channel model". This paper discusses these conceptual models in a sequential way, and ends providing thoughts on how they can be understood in a policy context.